To solve the system of equations using the elimination method, we first have the equations:
- \( y = x^2 - 2x - 2 \) (Quadratic)
- \( y = 2x - 6 \) (Linear)
Since both expressions are equal to \( y \), we can set them equal to each other to eliminate \( y \):
\[ x^2 - 2x - 2 = 2x - 6 \]
Now, let's rearrange and simplify the equation:
\[ x^2 - 2x - 2 - 2x + 6 = 0 \] \[ x^2 - 4x + 4 = 0 \] \[ (x - 2)^2 = 0 \]
This gives:
\[ x - 2 = 0 \implies x = 2 \]
Now, substituting \( x = 2 \) back into one of the original equations to find \( y \). We'll use the linear equation:
\[ y = 2(2) - 6 = 4 - 6 = -2 \]
Thus, we have one solution:
\[ (2, -2) \]
Now, to determine if there are any other solutions, we note that the equation \( (x - 2)^2 = 0 \) indicates that the only solution for \( x \) is \( 2 \), which means there is only one pair \((2, -2)\).
The answer is:
\[ (2, -2) \]
So, the correct response is:
(2, -2)